Cyberloafing Behavior And Work Environment: Between Distraction And Performance - The Impact on Work Satisfaction In The Administration Services of The Cianjur Registration Office - Abdullah, Abdullah; Nuraeni, Nuraeni (Dinasti Publisher, 2025)
This study aims to analyze the effect of cyberloafing behavior and work environment on employee performance with job satisfaction as a mediating variable in administrative services at the Population and Civil Registry Office of Cianjur Regency. Cyberloafing, which is the behavior of employees who use internet access for personal purposes during work time, can affect productivity and service quality. A positive work environment is expected to mitigate the negative impact of cyberloafing by creating an atmosphere conducive to improving employee performance. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to employees of Disdukcapil Cianjur and analyzed using path analysis techniques. The results showed that cyberloafing has a significant negative influence on employee performance, while a conducive work environment contributes positively to improving performance. Job satisfaction proved to be a mediating variable that strengthens the relationship between work environment and employee performance, but does not fully neutralize the negative impact of cyberloafing. This study concludes that improving the quality of population administration services requires better management of the work environment as well as supervision and training related to the professional use of the internet.